Description of a new species of Bradynobaenus (Hymenoptera: Bradynobaenidae) from Argentina, with a key to the females of the genus - Torréns, Javier; Roig-Alsina, Arturo (Zootaxa, 2009)
The new species Bradynobaenus riojanus (Hymenoptera: Bradynobaenidae) is described from two localities in the province of La Rioja, Argentina. It is closely related to B. chubutinus Brèthes. A revised key to the females of the genus is provided.